Unlocking protein-based biomarker potential for graft-versus-host disease following allogenic hematopoietic stem cell transplants - Iacobescu, Maria; Pop, Cristina; Uifălean, Alina; Mogoşan, Cristina; Cenariu, Diana; Zdrenghea, Mihnea; Tănase, Alina; Bergthorsson, Jon Thor; Greiff, Victor; Cenariu, Mihai; Iuga, Cristina Adela; Tomuleasa, Ciprian; et al. (Frontiers in Immunology, 2024)
Despite the numerous advantages of allogeneic hematopoietic stem cell transplants (allo-HSCT), there exists a notable association with risks, particularly during the preconditioning period and predominantly post-intervention, exemplified by the occurrence of graft-versus-host disease (GVHD). Risk stratification prior to symptom manifestation, along with precise diagnosis and prognosis, relies heavily on clinical features. A critical imperative is the development of tools capable of early identification and effective management of patients undergoing allo-HSCT. A promising avenue in this pursuit is the utilization of proteomics-based biomarkers obtained from non-invasive biospecimens. This review comprehensively outlines the application of proteomics and proteomics-based biomarkers in GVHD patients. It delves into both single protein markers and protein panels, offering insights into their relevance in acute and chronic GVHD. Furthermore, the review provides a detailed examination of the site-specific involvement of GVHD. In summary, this article explores the potential of proteomics as a tool for timely and accurate intervention in the context of GVHD following allo-HSCT.